A case of traumatic intrapleural foreign body with progressive supranuclear palsy removed by thoracoscopic surgery. (February 2023) - Koyama, Muneyuki; Matai, Kazuo; Kinoshita, Akiyoshi; Ishizaki, Shunta; Okazaki, Kouhei; Inoue, Masaya; Kodera, Keita; Hiramoto, Yuki; Arima, Toshihiko; Saito, Nobuhiro; Kobayashi, Miki; Yamazaki, Satoshi; et al.
Abstract: Traumatic intrathoracic foreign bodies are said to occur in many cases when the patient himself/herself is aware of the trauma. However, at the time of injury, the patient may sometimes be accompanied by loss of consciousness. We report a case of traumatic intrathoracic foreign body that was difficult to diagnose due to loss of consciousness at the time of injury. A 51-year-old female was brought to our emergency department with a fall trauma due to loss of consciousness while bathing. The head computed tomography and electrocardiogram showed no abnormalities, and the laceration of approximately 3 cm in length was found on the left side thorax, and it was sutured and the patient was sent home. Four days later, she returned to our hospital with a complaint of left anterior chest pain, and chest X-ray showed a left degree pneumothorax and mediastinal emphysema. She underwent semi-emergency thoracoscopic removal of the foreign body, and was discharged from the hospital on the fourth postoperative day. She had progressive supranuclear palsy, and her memory at the time of injury was not clear due to loss of consciousness caused by central autonomic neuropathy, and she also had dementia, making it difficult to interview her. She had no thoracic symptoms, and the glass fragment that had strayed into the thoracic cavity was not exposed outside the body, making the diagnosis difficult at the time of initial examination. When a patient with loss of consciousness is difficult to interview at the time of injury, it is advisable to perform an imaging examination appropriate for the site of injury, taking into consideration the presence of foreign bodies.